WESTERFELD, Scott. Feios. Tradução de Rodrigo Chia. Rio de Janeiro: Galera Record, 2010. - Couto, Edvaldo Souza; Goellner, Silvana Vilodre (Revista Entreideias: educação, cultura e sociedade, 2011)
Resenha do livro: WESTERFELD, Scott. Feios. Tradução de Rodrigo Chia. Rio de Janeiro-São Paulo, Galera Record, 2010.